Extensive Transcriptome Changes Underlying the Flower Color Intensity Variation in Paeonia ostii - Gao, Lexuan; Yang, Hongxing; Liu, Hongfeng; Yang, Ji; Hu, Yonghong (Frontiers in Plant Science, 2016)
Tree peonies are a group of traditional ornamental plants, especially in East Asia, with Paeonia ostii as one of the most important ancestral species. P. ostii has flowers with varying colors, ranging from nearly white, light pink to deep pink. However, few studies have been done to unravel the molecular mechanisms underlying the flower color intensity variation in plants. Based on comparative analyses of the pigment composition and transcriptomes of P. ostii with different flower color intensities, we found that the anthocyanin concentration was significantly correlated with the flower color intensity in P. ostii. Transcriptome analysis by RNA-Sequencing revealed 7,187 genes that were differentially expressed between flowers with different color intensities. Functional enrichment analysis of differentially expressed genes revealed multiple pathways possibly responsible for color intensity variation in P. ostii, including flavonoid biosynthesis, fatty acid oxidation, carbohydrate metabolism and hormone-mediated signaling. Particularly, while anthocyanin biosynthesis genes showing positive correlations between their expression and anthocyanin concentration in flowers, two transcription factors, PoMYB2 and PoSPL1, seem to negatively regulate anthocyanin accumulation by affecting the activation capacity of the MYB-bHLH-WDR complex, exhibiting an inverse relationship between their expression and anthocyanin accumulation. Our results showed that, although anthocyanin biosynthesis had a direct effect on the pigmentation of the P. ostii flower, other metabolic and hormone-mediated signaling pathways were also contributed to the flower color intensity variation in P. ostii, suggesting complex coordinated changes in the transcriptional network. Differential expression of genes encoding anthocyanin repressors seems to be the major factor responsible for the intensity variation in anthocyanin pigmentation in P. ostii.